(untitled) (Bangladesh Journal of Pharmacology, 2020)
The methanolic extract of Iphiona aucheri leaves and its n-hexane, chloroform and aqueous fractions were screened for phytochemicals, cytotoxic effects, total phenolic contents, antioxidant and anti-diabetic properties. The methanolic extract was assessed for its in vivo anti-diabetic effects. The results indicated the presence of alkaloid, protein and amino acids, carbohydrates, glycosides, flavonoids, and saponins along with the highest brine shrimp lethality (90.7 ± 1.8%), α-amylase inhibition (60.2%) and free radical scavenging properties. The diabetic control indicated a significant (p<0.05) decrease in weight and high-density lipoprotein and elevated level of blood glucose, bilirubin, creatinine, urea, triglyceride, low density lipoprotein, very low-density lipoprotein, transaminases, and alkaline phosphatase. All these changes were restored significantly (p<0.05) by treatment of diabetic rats with methanolic extract of I. aucheri. The results show the potential of I. aucheri as a source of therapeutic compounds against diabetic, hyperlipidemia and free radical associated disorders.